Measurement of the eco-environmental effects of urban sprawl: Theoretical mechanism and spatiotemporal differentiation. (October 2019) - Chen, Danling; Lu, Xinhai; Liu, Xu; Wang, Xue
Highlights: A theoretical framework for environmental impacts of urban sprawl was introduced. A PSR index system was built to measure eco-environmental effects of urban sprawl. Spatiotemporal differentiation of urban sprawl eco-environmental effects was observed. Considering eco-environmental effects in urban planning is feasible and promising. Abstract: Urban sprawl and its eco-environmental impacts are crucial components of global environmental change research, and a core issue for sustainable development. In this study we used a Pressure-State-Response (PSR) system to develop a theoretical framework, in which the total eco-environmental effects of urban sprawl (EEUS) were divided into pressure, state, and response. A corresponding index system was then constructed to evaluate the different kinds of EEUS in China's 30 provinces from 2003 to 2015, and temporal and spatial characteristics are explored through spatial autocorrelation analysis. We found that 1) pressure, state and response EEUS not only had differences but also strong connections. These three kinds of eco-environmental effects also had different causal mechanisms and their contributions to the total EEUS were different. 2) The pressure, state and response, as well as the total EEUS, increased from 2003 to 2015. However, there were clear disparities in EEUS across the eastern, central, western and northeast regions. EEUS results for the eastern and northeast regions were higher than in the central and western regions. 3) There was significant spatial dependence and heterogeneity in EEUS. Overall, the spatial difference in EEUS was mainly caused by "HH" and "LL" cluster types. These results have significant implications for theoretical guidance and policy efforts. We conclude that a better eco-environment in the process of urban sprawl can be achieved by improving the quality of urban development and enhancing government management.